A review of methods for the reconstruction and analysis of integrated genome-scale models of metabolism and regulation. (17th September 2020) - Cruz, Fernando; Faria, José P.; Rocha, Miguel; Rocha, Isabel; Dias, Oscar
Abstract : The current survey aims to describe the main methodologies for extending the reconstruction and analysis of genome-scale metabolic models and phenotype simulation with Flux Balance Analysis mathematical frameworks, via the integration of Transcriptional Regulatory Networks and/or gene expression data. Although the surveyed methods are aimed at improving phenotype simulations obtained from these models, the perspective of reconstructing integrated genome-scale models of metabolism and gene expression for diverse prokaryotes is still an open challenge.